2014
DOI: 10.1002/maco.201407687
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion behavior of TiO2‐coated Ti–6Al–7Nb surfaces obtained by anodic oxidation in sulfuric or acetic acid

Abstract: The morpho-structural and electrochemical properties of the oxide film formed on the implants surface play a decisive role for the bio-compatibility of titaniumbased prosthesis. The aim of the present work is to investigate and compare the corrosion behavior of titanium dioxide (TiO 2 ) coated Ti-6Al-7Nb prepared by anodic oxidation in two different electrolytes (1 M acetic acid (CH 3 COOH) and sulfuric acid (H 2 SO 4 ) solutions) and at two different oxidation potentials. The corrosion behavior of oxidized sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 31 publications
1
7
1
Order By: Relevance
“…Table 2 shows that for untreated alloy, the outer porous layer resistance, R o , value of 154 ohm cm 2 was obtained. Other studies [15,17,33] have reported values of 333, 800, and 287 ohm cm 2 , respectively, for this alloy in Hank s solution, somehow different to those used in this work. This value increased as the oxidation time increased, reaching a highest value of 59,500 ohm cm 2 for specimen oxidized during 3 h. A further increase in the oxidation time decreased the value for R o .…”
Section: Electrochemical Impedance Spectroscopy Testscontrasting
confidence: 82%
See 4 more Smart Citations
“…Table 2 shows that for untreated alloy, the outer porous layer resistance, R o , value of 154 ohm cm 2 was obtained. Other studies [15,17,33] have reported values of 333, 800, and 287 ohm cm 2 , respectively, for this alloy in Hank s solution, somehow different to those used in this work. This value increased as the oxidation time increased, reaching a highest value of 59,500 ohm cm 2 for specimen oxidized during 3 h. A further increase in the oxidation time decreased the value for R o .…”
Section: Electrochemical Impedance Spectroscopy Testscontrasting
confidence: 82%
“…On the other side, the inner compact barrier layer resistance value, R i , was 331,000 ohm cm 2 for untreated specimen, whereas other researchers reported values of 551,000, 1.0 × 10 6 , and 6.4 × 10 6 ohm cm 2 , respectively [15,17,33]. Similar to the value for the outer porous layer resistance, R o , the value for R i increased as the oxidation time increased, reaching its highest value for specimen oxidized during 3 h, decreasing for a further increase in the oxidation time.…”
Section: Electrochemical Impedance Spectroscopy Testsmentioning
confidence: 85%
See 3 more Smart Citations